Causative Factors of Cost Overrun in Building Projects of Pakistan - Sohu, Samiullah; Abdullah, Abd Halid; Nagapan, Sasitharan; Memon, Nafees Ahmed; Yunus, Riduan; Hasmori, Muhammad Fikri (International Journal of Integrated Engineering, 2019)
Cost overrun is cost of the project exceeds the approved cost of the project at the time of tender. Cost overrun or budget overrun is the main problem in the construction of building projects in Sindh Province of Pakistan. To attain the main objective of the research deep literature review was carried out and total 64 factors of cost overrun were identified in construction industry. A questionnaire was developed and distributed among 28 well experienced experts having more than 20 years in building projects. Collected data was analyzed by average index method. Results shows that main and causative factors of cost overrun were financial difficulties faced by client, slow information between parties, change in price of material, delay of design, poor site management, cash and payment problem faced by contractor and delay in decision making. This research can help petitioners of building projects to overcome these main and causative factors of cost overrun or budget overrun.